PERAN GURU KELAS DALAM MEMBENTUK KARAKTER SISWA MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA - Armianti, Riska (Jurnal Sintaksis, 2025)
This study aims to examine the role of classroom teachers in shaping students' character through Pancasila education in elementary schools. The method used is a literature study by analyzing various sources related to character education. The study results indicate that classroom teachers serve as role models, mentors, motivators, and evaluators in instilling Pancasila values such as discipline, responsibility, tolerance, and mutual cooperation. Pancasila education has been shown to help students develop positive attitudes and prevent negative behaviors such as bullying. However, the character-building process still faces challenges such as environmental influences, lack of parental support, and teachers' limited understanding. This study concludes that collaboration between teachers, schools, and families is crucial to optimizing character education.